Bridging Policy and Practice: Institutional Support and Program Sustainability for Returned Migrant Workers - Hazhiyah Nurina Idzni; Rizki Syafril (Journal of Educational Management Research, 2026)
This study aims to analyze the sustainability of return migrant empowerment programs and identify the factors that hinder their long-term implementation. The research employed a qualitative descriptive approach, with data collected through in-depth interviews, observation, and document analysis. The data were analyzed using the interactive model of Miles and Huberman, consisting of data condensation, data display, and verification of findings. The results indicate that the empowerment program has achieved partial sustainability but has not yet developed into a fully integrated and systematic reintegration mechanism. Institutional sustainability remains constrained by dependence on individual actors, limited organizational continuity, and weak cross-sector collaboration. Human resource development has improved participants’ skills; however, the impact remains uneven due to limited post-training mentoring and differences in entrepreneurial capacity. Policy support is relatively strong at the regulatory level but remains limited in operational implementation, particularly regarding sustainable funding and coordinated support systems. The main barriers identified include the absence of continuous programs, weak monitoring mechanisms, unstable participant commitment, and limited private-sector involvement. The study implies that strengthening sustainable reintegration requires institutionalized post-training assistance, formal multi-stakeholder partnerships, and more stable funding mechanisms to ensure that empowerment outcomes become systemic rather than dependent on individual success.